2022
DOI: 10.1021/acs.analchem.2c01286
|View full text |Cite
|
Sign up to set email alerts
|

Ag Nanoparticles with Ultrathin Au Shell-Based Lateral Flow Immunoassay for Colorimetric and SERS Dual-Mode Detection of SARS-CoV-2 IgG

Abstract: Immunoglobulin detection is essential for diagnosing progression of SARS-CoV-2 infection, for which SARS-CoV-2 IgG is one of the most important indexes. In this paper, Ag nanoparticles with ultrathin Au shells (∼2 nm) embedded with 4-mercaptobenzoic acid (MBA) (Ag MBA @Au) were manufactured via a ligand-assisted epitaxial growth method and integrated into lateral flow immunoassay (LFIA) for colorimetric and SERS dual-mode detection of SARS-CoV-2 IgG. Ag MBA @Au pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 54 publications
0
66
0
Order By: Relevance
“…Recently, Liang et al reported a colorimetric and SERS dual-mode lateral flow immunoassay for the qualitative and quantitative detection of SARS-CoV-2 IgG, with a detection limit of 0.52 pg/mL in 15 min ( Figure 5 a). The excellent performance is related to the delicate structure of AgMBA@Au, prepared by a ligand-assisted epitaxial growth method [ 57 ]. Gao et al constructed a triple-mode biosensor to detect RNA in SARS-CoV-2 by using the colorimetric, SERS, and fluorescence properties of Au nanoparticles [ 58 ].…”
Section: Fluorescence Biosensor For Sars-cov-2 Diagnosismentioning
confidence: 99%
“…Recently, Liang et al reported a colorimetric and SERS dual-mode lateral flow immunoassay for the qualitative and quantitative detection of SARS-CoV-2 IgG, with a detection limit of 0.52 pg/mL in 15 min ( Figure 5 a). The excellent performance is related to the delicate structure of AgMBA@Au, prepared by a ligand-assisted epitaxial growth method [ 57 ]. Gao et al constructed a triple-mode biosensor to detect RNA in SARS-CoV-2 by using the colorimetric, SERS, and fluorescence properties of Au nanoparticles [ 58 ].…”
Section: Fluorescence Biosensor For Sars-cov-2 Diagnosismentioning
confidence: 99%
“…The fifth route is based on NP accumulation reactions [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. This strategy has been generally used in flat substrate-based systems, such as the lateral flow assay (LFA), µ-paper-based analytical device (µ-PAD), and paper-based dipstick system [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. These systems rely on the capillary action of fluids and colored NPs.…”
Section: Colorimetric Detection and Monitoring Strategies Of Bacteria...mentioning
confidence: 99%
“…The concentrated NPs act as colorimetric labels or color generation factors. Colored NPs used for colorimetric detection include AuNPs, silver NPs (AgNPs), and colloidal carbon [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Red AuNPs are one of the widely used colorimetric labels because of their bright color, high stability, and high biocompatibility [ 80 ].…”
Section: Colorimetric Detection and Monitoring Strategies Of Bacteria...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, high requirements for skilled operators and time-consuming steps limit their application for large-scale screening. Compared with these methods, lateral flow immunoassay (LFIA) owns its unique advantages of short reaction time, low-cost detection, portability, and user-friendliness which are suitable for screening, on-site, and rapidity to diagnose SARS-CoV-2 [ 20 , 21 ]. However, the traditional colloidal gold nanoparticles (AuNPs)-based LFIA has poor quantitative ability, high false negative rates and limited sensitive, due to the absence of readout system and the single signal of colorimetric [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%